Phosphorus and ammonium removal characteristics from aqueous solutions by a newly isolated plant growth-promoting bacterium. Issue 20 (5th September 2020) - Daly, Imen; Jellali, Salah; Mehri, Ines; Reis, Maria A. M.; Freitas, Elisabete B.; Oehmen, Adrian; Chatti, Abdelwaheb
ABSTRACT: An indigenous plant growth-promoting bacterium isolated from Peganum Harmala rhizosphere in the arid ecosystem was found to solubilize and accumulate phosphates. This isolate was identified as Pseudomonas sp . (PHR6) by partial 16S rRNA gene sequence analysis. Controlled batch experiments on nutrients removal by this isolate in mineral medium showed relatively high efficiencies after 24 h of aerobic incubation with average values of 117.59 and 335.38 mg gVSS −1 for phosphorus (P-PO4 ) and nitrogen (N-NH4 ), respectively. Furthermore, the strain performed heterotrophic nitrification ranging from 48.81% to 84.24% of the total removed nitrogen. On the other hand, the experimental results showed that a short idle period (24 h) significantly enhanced P accumulation (up to 95%) and N assimilation (up to 50%) of the total removed amounts. However, long idle period (20 days) revealed firstly aerobic phosphorous release phase succeeded by another removal one within 24 h of incubation. Overall, the idle treatment enhances P removal efficiency from the mineral liquid medium without significant effects on N-NH4 removal performance. The isolated strain showed also significant nutrient removal ability from synthetic wastewater providing an accumulated fraction of 98% from the total removed phosphorus amount. This study highlights the potential contribution of the selected rhizobacterium PHR6 to both environmental nutrient recycling and pollution control especially regarding phosphorus. GRAPHICAL ABSTRACT: